Recent tendencies in the prevention and treatment of menopausal syndrome - V N Prilepskaya; I K Bogatova; V E Radzinskiy (IP Berlin A.V., 2016)
The results of a multicenter, double-blind, placebo-controlled randomized study of therapeutic efficacy and safety of peptide structure of Pineamine® in neuro and psycho-emotional manifestations of the climacteric syndrome in women.Materials and methods. We observed 120 women aged 45-60 years in postmenopausal women (more than 1 year after the last menstrual period) with neurovegetative and psycho-emotional symptoms. After the step of screening patients met the criteria for inclusion/non-inclusion were randomized into 3 groups at a ratio of 1:1:2, namely: the placebo group - 30 patients (placebo rate of 1 mg daily, intramuscularly, the duration of 10 days); group Pineamine®-1 (P1) - 30 patients (one course of Pineamine® - 10 mg daily, intramuscularly, the duration of 10 days) and a group of Pineamine®-2 (P2) - 60 patients, with two 10-day courses Pineamine® (10 mg daily, intramuscularly, duration 10 days). On the 90th day all the patients underwent a second 10-day course: the placebo group - a drug placebo 10 mg intramuscularly; group P1 - a drug placebo 10 mg intramuscularly; group P2 - intramuscular Pineamine® - 10 mg. The study conducted 7 visits. The main method of confirming the effectiveness of the drug, is the dynamics of the Kupperman index (vegetative and psycho-emotional symptoms). In addition, we studied the number of adverse events and adverse reactions associated with the use of the drug. We investigated the vital parameters (blood pressure, heart rate, respiratory rate, ECG) and the entire range of standard and special haematological and biochemical indices of the blood levels of thyroid hormones, female hormones, EEG was performed. To closely monitor the condition of the endometrium by ultrasound of the pelvic organs, and according to endocervical cytology (Pap smear). All patients performed densitometry of femur and spine.Results of the study. It was found that the original 3 groups of patients didn't differ by demographic characteristics, severity of menopausal symptoms and laboratory data and instrumental performance. For various reasons, dropped out of the study 19 patients and populations "protocol" amounted to 101 patients. The primary efficacy were evaluated in patients of all groups at 90 and 180 days of treatment. Analysis of the results showed that the primary criteria for efficacy of Pineamine® - reducing the severity of menopausal syndrome (modified Kupperman Index) measured at one or more points from baseline dannymi-achieved in the population of "efficiency", as well as in the population "protocol". Thus, the group of patients receiving drug treatment by Pineamine® (P1 and P2) were significantly different from the vehicle group (in the population of "effectiveness" p=0.04; in the population "protocol" p=0.02). In analyzing the results of the data obtained at day 180 in group P2 (two courses of Pineamine®) there was a clear difference from placebo in a population of "effectiveness", and the population "protocol" (p=0.04). During this period it is determined that the basis of the effectiveness of drug therapy PineaminR of its impact on neurovegetative symptoms of menopausal syndrome (significant dynamics in all populations in the 90 and 180 day).Secondary performance criteria - the dynamics of total score of Kupperman index and the difference compared with its original data - are also achieved in the research process. This indicator of neuroautonomics reaffirmed the role of the segment index (p=0.047). In assessing the data on the tolerability and safety of the drug noted 22cases of adverse events, found mainly in the groups of women who received injections of Pineamine®.Conclusion. Primary and secondary efficacy criteria reliably prove that the domestic product peptide structure of Pineamine® - an effective drug for the treatment of menopausal syndrome. It was established that its mechanism of action is aimed primarily at neurovegetative climacteric syndrome. Security of Pineamine confirmed by the absence of negative results of instrumental - laboratory parameters in all study participants.